2021
DOI: 10.37111/braspenj.2020354012
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores de qualidade da terapia nutricional enteral são ferramentas úteis para o monitoramento em pacientes com câncer avançado em cuidados paliativos?

Abstract: Introduction: Enteral nutritional therapy (ENT) in patients with advanced cancer in palliative care should be directed towards a better quality of life, being important its monitoring so that the patient has access to the best that the therapy can offer. The objective of this study was to apply the quality indicators of ENT in patients with advanced cancer in palliative care. Methods: Descriptive, observational study with a quantitative approach. Seven ENT quality indicators proposed by the International Life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For nursing, summarizing the information of the investigated IQNT becomes essential in the sense of strategically directing care to the need for the nutrition of the oncological patient to optimize treatment and ensure better quality of life. 30 The review identified that the authors' profile was composed mostly of nutritionists, [21][22][23][25][26][27][28] although nursing is responsible for monitoring the indicator under analysis. 13 In Brazil, specific legislation 31 standardizes the performance of the nursing team in the oro/nasogastric and transpyloric probing and highlights the crucial role of the nurse in the process of installing the device, choosing the route of administration together with the doctor, in addition to registration, patient evaluation and monitoring of complications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For nursing, summarizing the information of the investigated IQNT becomes essential in the sense of strategically directing care to the need for the nutrition of the oncological patient to optimize treatment and ensure better quality of life. 30 The review identified that the authors' profile was composed mostly of nutritionists, [21][22][23][25][26][27][28] although nursing is responsible for monitoring the indicator under analysis. 13 In Brazil, specific legislation 31 standardizes the performance of the nursing team in the oro/nasogastric and transpyloric probing and highlights the crucial role of the nurse in the process of installing the device, choosing the route of administration together with the doctor, in addition to registration, patient evaluation and monitoring of complications.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In addition, cancer is one of the main underlying diseases of hospitalized adult patients in Brazil. 39 In analytical corpus in which the IQNT goal was not met [21][22][23][24][25][26]29 the most prevalent cancers were head and neck 21,26 , gastrointestinal tract 21,26 , gynecological 21,26 and urological. 21,29 In those who have reached the goal 23,27,28 the most identified cancers were head and neck 23 gastrointestinal tract 23,27 , breast 23,28 and lung.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations